Teaching with A Rounder Sense of Purpose: a survey study on education for sustainable development competences in Latin America - Álvarez-Vanegas, Alejandro; Rieckmann, Marco; Lopera Pérez, Marisol; Aguirre, Patricia M. (Frontiers in Education, 2024)
Through support and guidance in fostering competences in ESD, educators can help students to evolve into engaged citizens capable of addressing the current ecological crisis. However, in order to provide effective guidance, educators need to become proficient in sustainability. In this line, this study investigates i) the depth of knowledge about sustainability (including teaching for sustainability), ii) stances towards the Sustainable Development Goals, and iii) competences that Latin American university educators perceive they possess. A survey was designed, including elements from previously validated instruments and using the competences framework A Rounder Sense of Purpose. It was answered by educators from Latin America (N = 197), mainly Colombia and Ecuador. Through a statistical analysis, ranks were developed, and further analyses were made. Although this research is based on the self-perception of respondents, findings suggest that educators have some knowledge about ESD. However, there is room for improvement, particularly in terms of action. Additionally, there are inconsistencies between the competences they aim to develop in their students and the ones they currently possess. Such an assessment had not been done specifically for the Latin American context, and the A Rounder Sense of Purpose framework of competences had yet to be explored with a large sample of educators. The results of this research will allow to offer of a more adequate and pertinent capacity-building program for university educators.